Cervical Adenocarcinoma: A Comparison of the Reproducibility of the World Health Organization 2003 and 2014 Classifications. Issue 2 (April 2018) - Sar, Aylin; Duan, Qiuli; Khalil, Moosa; DiFrancesco, Lisa M.; Ewanowich, Carol; Lytwyn, Alice; Djordjevic, Bojana; Itani, Doha; Lee, Sandra; Köbel, Martin; Glaze, Sarah; Park, Elena; et al.
Abstract : Objective: The aim of the study was to compare the reproducibility of malignant glandular tumors of the uterine cervix classified per World Health Organization (WHO) 2003 and 2014. Materials and Methods: Two pathologists reviewed 228 cases composed of adenocarcinoma in situ and 22 adenocarcinoma histotypes and selected 405 representative hematoxylin and eosin slides, which were digitally scanned. Six other pathologists (3 gynecological and 3 anatomical) independently reviewed and classified the images per both WHO classifications. One year later, they classified a random sample of 25 cases. Inter- (inter-OR) and intra-observer (intra-OR) reproducibility of the 6 pathologists and separately for gynecological compared with anatomical pathologists was tested using κ statistics. Results: Both classifications were collapsed into 6 categories as benign, adenocarcinoma in situ, and mucinous, endometrioid, rare, and adenosquamous-miscellaneous carcinomas. WHO 2014 had an additional category: endocervical adenocarcinoma, usual type. Inter-observer κ values were more reliable than the intra-OR results based on 95% CIs. The average inter-OR κ values with both classifications were moderate between the 6 pathologists and between the 3 anatomical pathologists. In contrast, they were substantial between the 3 gynecological pathologists. With both classifications, the average intra-OR κ values of the 6 pathologists and both pathologist groups trended toward substantial. Conclusions: Reproducibility among 6 pathologists is unaffected by changes in the WHO 2014 classification and averages moderate between different and trends toward substantial between the same pathologist. Reproducibility between different pathologists can improve to substantial when they have expertise in gynecological pathology.